PENGEMBANGAN POTENSI WISATA KAMPUNG TEMATIK KOKOLAKA DI KELURAHAN JATIREJO KECAMATAN GUNUNGPATI, KOTA SEMARANG - Salsabila, Safina (Jurnal Riptek, 2024)
Thematic Village is one of Semarang City Government programst to alleviate poverty problems in Semarang City. Thematic Village is part of the "Gerbang Hebat" which aims to reduce poverty and unemployment through harmonization of economic education which was established since 2016. KOKOLAKA or Thematic Village of Kolang-Kaling is one of the thematic villages located in Jatirejo Village, Gunungpati District, Semarang City since 2017 with the main potential is kolang-kaling products. In this study, through profiling of KOKOLAKA Thematic Village tried to identify potential and problems that exist and formulate alternative strategies through SWOT method. The results showed that KOKOLAKA Thematic Villages need to optimize online sales of kolang-kaling products and improve the quality of tourist facilities in KOKOLAKA Thematic Village. Through the alternative strategies, the author hoped that it can help KOKOLAKA Thematic Village to be a sustainable tourism destination by highlighting the local potential of the kolang-kaling product.Â